Application of Quasi Homogeneous diffusion models and film broadcast on Ion Exchange Kinetics of Hexavalent Chromium in Agitated Systems - Armijo C., Javier (2003)
Experiments were carried-out for exchange reaction between ions dichromate Cr207 2- solution and resín type DOWEX 1X4. It is reported the concentration of Cr+6 versus raaction time for resin wetghts between O.1 to 0.8 grams and for initial concentrations of 50, 100 and 200 ppm. The experimental data are correlations with the models of homogeneous quasi ditfusion and diflusion control1ed by the liquid film resistance, The experiments show that is required a weight of resin equal to O, 75 grams to reduce the Cr+6 concentration to 1 ppm in 1 hours.